Synthesis And Characteriztion Of Non-Ionic Surfactant - Princilla, Leong (Universiti Malaysia Sarawak (UNIMAS), 2013)
Non-ionic surfactant derived from Kojic acid was synthesized and analyzed. The synthesis of non-ionic surfactant involved the esterification of stearic acid-polyethylene glycol ester with Kojic acid. The structure of the synthesized non-ionic surfactant was confirmed by using FTIR, 1H NMR and 13C NMR. The properties of synthesized compound such as critical micelle concentration (CMC), cloud point, wetting time, foaming and foam stability, pH value and also emulsion stability was investigated. The synthesized compound showed high value of cloud point (91oC) and wetting time (139 seconds) in addition to their low CMC at 0.0008M. As the number of ethylene oxide chain units in the synthesized compound higher, the foaming and foam stability also higher, which is 71.67 %. The synthesized compound has pH value of 5.45 where the common non-ionic surfactant posses pH value at the range 3 to 12. Moreover, the synthesized non-ionic surfactant showed lower emulsification power (25 seconds) that makes them useful for wide ranges of applications.